SLANG WORDS HARNESSING THE LESBIAN COMMUNITY IN BONDOWOSO DISTRICT - Wahyuningsih, Agung Tri; Nadhifah, Siti; Anam, Syamsul (Linguistik, Terjemahan, Sastra (LINGTERSA), 2022)
Lesbians are primarily residents of the Greek island of Lesbos. The term gained currency after Sappho, a poet from Lesbos around 600 BC, depicted the state of a female's blistering emotional and erotic lodestone toward another female [1]. While there has been an increase in tolerance and a decrease in discrimination in recent years, and some studies have been conducted on lesbianism and lesbian-related linguistic features, lesbianism and lesbian-related linguistic features have received significantly less attention than gay men's homosexuality [2]. Taking up this issue, this research is determined to elucidate the specific language variation used by the Bondowoso district's lesbian community. As the concept of lesbian-specific words is reformed and deconstructed, this investigation seeks to unearth the meaning of the language variety referred to as slang. Additionally, to complete this research, some sociological factors influencing the use of slang [3] are examined. The interview is conducted to elicit information about the sociological factors that contribute to speakers' use of slang in their community. The result indicates that the majority of slang words are derived from English and refer to gender roles, physical characteristics/appearance, types of relationships, and sexual activities. Bondowoso's lesbian community adapts slang terms used by lesbians worldwide phonologically. Sociological factors and reasons indicate that this queer society views self-identification as a lesbian as the most significant identity because it has ramifications for other attributions.